Performance evaluation of control networks Ethernet, ControlNet, and DeviceNet. - Feng-Li Lian
Many different network types have been promoted for use in control systems. In this article, we compare three of them: the Ethernet bus, with carrier sense multiple access with collision detection, token-passing bus (e.g., ControlNet), and controller area network bus (e.g., DeviceNet). We consider how each control network can be used as a communication backbone for a networked control system connecting sensors, actuators, and controllers. A detailed discussion of the medium access control sublayer protocol for each network is provided. For each protocol, we study the key parameters of the corresponding network when used in a control situation, including network utilization, magnitude of the expected time delay, and characteristics of time delays. Simulation results are presented for several different scenarios, and the advantages and disadvantages of each network are summarized
Keywords: ControlNet; DeviceNet; Ethernet; Control networks; Control systems; Controller area network; Medium access control; Protocol; Time delay; Token-passing bus